2004
DOI: 10.1097/00001888-200406000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine–Pediatrics Residency Training: Current Program Trends and Outcomes

Abstract: Compared with previous studies, a greater proportion of residents who recently entered med-peds programs completed their dual training, and a larger percentage of graduates are seeing both adults and children. The proportion of residents entering subspecialty residencies has increased significantly, but the proportion of graduates in academic careers has remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…These programs have also contributed to solutions in physician shortage areas and pediatrics subspecialty shortage areas. 13 Med-peds graduates practice in a wide variety of settings, including ambulatory centers, inpatient wards, and intensive care units. 14 In the present study, we examined the residents' training experiences and whether these combined training programs are meeting the diverse educational needs of med-peds residents and fostering the future plans of medpeds residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These programs have also contributed to solutions in physician shortage areas and pediatrics subspecialty shortage areas. 13 Med-peds graduates practice in a wide variety of settings, including ambulatory centers, inpatient wards, and intensive care units. 14 In the present study, we examined the residents' training experiences and whether these combined training programs are meeting the diverse educational needs of med-peds residents and fostering the future plans of medpeds residents.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is on the upper end of the range of 77% to 95% reported in previous studies. 8,9,[13][14][15][16][17] This higher percentage of residents planning to care for adults and children may be related to a number of factors; for example, there are increasing numbers of med-peds physicians in practice in the community available to work with, there are greater numbers of residents training in combined clinics, and there is a greater availability of med-peds role models.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no delineation of how much care was provided to each age group. 3 Lannon et al 4 completed the most recent survey of internal medicine-pediatric graduates in 1995 and reported results in 1999. This study found that only 4% of those who completed training from 1985 to 1995 provided no care to children who are younger than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 At the individual level, the pass rate for examinees on the American Board of Internal Medicine and ABP examinations were quite high, at 97% and 96%, respectively. 1 This cohort of individuals seems to have higher pass rates on the ABP Certifying Examination (CE) than the overall pass rate for individuals. [3][4][5] Although the individual dually trained examinee data have been evaluated in the past, the performance of residencies based on the presence or absence of a dual internal medicine-pediatrics accredited program has not been studied.…”
Section: Introductionmentioning
confidence: 99%